Scurvy induced by obsessive-compulsive disorder - Vieira, Amanda A. O. [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Gaiolla, Rafael D. [UNESP]; Okoshi, Marina P. [UNESP]; Duarte, Daniella R. [UNESP]; Matsubara, Luiz S. [UNESP]; Inoue, Roberto M. T. [UNESP]; Azevedo, Paula S. [UNESP]; Polegato, Bertha F. [UNESP]; Zornoff, Leonardo A. M. [UNESP]; Paiva, Sergio A. R. [UNESP] (BMJ, 2009)
Historically, scurvy has been associated with sailors of great navigational epochs. This disease has been known since ancient Egypt, but nowadays it is almost forgotten. Although its prevalence has decreased over the centuries, scurvy is still present in developed countries. A 61-year-old man was referred to hospital with a 30-day history of anorexia, fatigue, gingival bleeding and ecchymosis of the arms and legs. On physical examination he presented gingival hypertrophic lesions, signs of chronic periodontitis and petechial rash, and several bruises on his arms and legs. A food frequency questionnaire revealed a long history of poor diet, with no vegetables or fruit. The patient had ingested only chocolate milk and cookies for the last 10 years due to fear of pesticides being present in foods of vegetable origin. A diagnosis of scurvy induced by obsessive-compulsive disorder was suspected, and after vitamin C supplementation there was a marked improvement of symptoms.